Institutionalising Civilian Control of the Military in New Democracies: Theory and Evidence from South Korea - David Kuehn (German Institute of Global and Area Studies (GIGA), 2016)
This paper aims to answer the question of how and under what circumstances civilian control can be established in newly democratised nations. To do this, I propose a new theoretical argument that conceives of the process of institutionalising civilian control in new democracies as a series of power struggles between the democratically elected civilians and the military leadership. The outcome of these power struggles depends on the respective bargaining power of civilians and the military, which is in turn a function of (1) the willingness of civilians to challenge the military's institutional prerogatives and the military's willingness to defend them and (2) each party's ability to bear the costs of a civil-military conflict. To illustrate and assess the argument, I derive a number of propositions about the expected development of civil-military relations after the transition to democracy and the possible outcomes of civil-military power struggles, subsequently testing them via an in-depth case study of civil-military relations in post-transition South Korea.
Keywords: 300; civilian control; civil-military relations; democratisation; military; South Korea